AR Flood - Tua, Yong Liang (2023)
Flash floods have become increasingly severe in Malaysia due to overdevelopment of cities, causing significant damage and disruption. The Malaysian government reported MYR 6.1 billion in damages from recent floods. Augmented reality (AR) and Rapid Application Development (RAD) have been proposed as solutions to help mitigate the impact of floods in the country. AR technology provides an interactive experience of the real-world environment by superimposing computer-generated elements on top of the actual world. With AR Flood, Malaysians can preview the severity of floods in their area and view real-time water levels provided by the Ministry of Environment and Water. The RAD model focuses on developing applications rapidly and efficiently through continuous feedback, making it more likely to be accepted by end users. The RAD life cycle structure consists of four phases: Requirements Planning, User Design, Construction, and Cutover. This paper presents a proposal to implement AR Flood, an augmented reality application, to help mitigate the impact of floods in Malaysia. The application will provide real-time information on water levels, allowing Malaysians to preview the severity of floods in their area. The information will be categorized into normal, alert, warning, and danger levels, giving users a clear understanding of the predicted flood situation. The implementation of AR Flood will be based on the Rapid Application Development (RAD) model, which focuses on developing applications rapidly and efficiently through continuous feedback. The RAD life cycle structure ensures that the development process is followed and includes four fundamental phases: Requirements Planning, User Design, Construction, and Cutover. This proposal aims to provide a practical solution to the problem of flash floods in Malaysia, helping to mitigate their impact and provide a safer and more informed environment for Malaysians.